Reproductive Biology of Common Carp(Cyprinus carpio L.) from AL-Gharraf Canal at Wasit province –Iraq II. Fecundity of Females - Hamady, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
From September 2002, monthly samples of common carp (Cyprinus carpio L.) were collected from two stations al AL-Gharraf canal. The results of this study revealed that the relationship between fecundity and total length , body weight and age can be  expressed by the following equations:  Log F=2.049+1.059 Log W.     r =0.98 Log F=1.173+2.534 Log L.     r =0.96 Log F=3.844+2.197 Log A.     r =0.87 The range of the absolute fecundity of 20 female fishes were 50910 â€“ 1008514 eggs and the relative fecundity was 177 eggs/g. The average egg diameter was 1.52 mm in ripe female and it ranged from 0.99mm to 1.64mm. There were three peaks of Ganado somatic index in the female fishes appeared at August ,November and February While in the male fishes appeared at November, January and April, it was at least two spawning seasons in the year.